2019
DOI: 10.1136/bmjopen-2018-027049
|View full text |Cite
|
Sign up to set email alerts
|

Real-world persistence and adherence with oral bisphosphonates for osteoporosis: a systematic review

Abstract: ObjectivesThis study examined patient adherence and persistence to oral bisphosphonates for the treatment of osteoporosis in real-world settings.MethodsA systematic review was completed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Allied and Complementary Medicine Database (AMED), Database of Abstracts of Reviews of Effects (DARE), Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
98
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 109 publications
13
98
3
2
Order By: Relevance
“…The currently available data on adherence and persistence to osteoporosis medications have several limitations. First, the available data was mostly self-reported, introducing social desirability and recall bias, or may not be true values due to the use of prescription data and time until last prescription refill [ 6 ]. In addition, this resulted also in an increased risk of bias of missing outcome data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently available data on adherence and persistence to osteoporosis medications have several limitations. First, the available data was mostly self-reported, introducing social desirability and recall bias, or may not be true values due to the use of prescription data and time until last prescription refill [ 6 ]. In addition, this resulted also in an increased risk of bias of missing outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis medications have shown to be effective in fracture risk reduction [ 3 ]; however, it is well known that adherence to osteoporosis medications is poor and suboptimal, varying from 34 to 75% in the first year of treatment [ 4 , 5 ]. Persistence levels at 1 year were estimated between 18 and 75% [ 6 ]. This suboptimal adherence and persistence leads to increased fracture rate (up to 30%) and worse health outcomes (more subsequent fractures, lower quality of life, and higher mortality), substantially deteriorating the cost-effectiveness resulting from these medications [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Persistence has been shown to have the most influence on cost-effectiveness [ 40 ]. Real-world persistence data with oral bisphosphonates were derived from a recent systematic review suggesting that the mean persistence was 53% at 6 months, 46% at 1 year, 37% at 2 years and 31% at 3 years [ 41 ]. For patients who stopped taking their therapy, the treatment cost immediately stopped and the offset (assumed as a period similar to duration on therapy) period started at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple meta-analyses and systematic reviews have shown that bisphosphonates are effective in decreasing the risk of various types of bone fractures ( Feng et al, 2013 ; Brown et al, 2014 ). However, it is widely acknowledged that compliance (the extent to which a patient acts in accordance with the prescribed interval and dose of a dosing regimen) and persistence (duration of time from initiation to discontinuation of the therapy) with oral osteoporosis medications are poor ( Imaz et al, 2010 ; Hiligsmann et al, 2012a ; Hiligsmann et al, 2012b ; Fatoye et al, 2019 ). A recent observational study estimated that 53% of the study population achieved a medication possession ratio (MPR) of 80% or higher 6 months after initiating therapy, and the equivalent value for 7–12 months was only 43% ( Kothawala et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%